2010
DOI: 10.1002/ejlt.201000097
|View full text |Cite
|
Sign up to set email alerts
|

Preservative effect of an organic acid‐icing system on chilled fish lipids

Abstract: This study provides a first approach concerning a novel chilling strategy, which employs a mixture of different preservative organic acids (ascorbic, citric and lactic) in the icing medium. Thus, ice prepared from water including two different concentrations of a commercial acid mixture-formula (800 and 400 ppm; C-800 and C-400 conditions, respectively) were applied as icing system to three important commercial fish lean species (hake, Merluccius merluccius; megrim, Lepidorhombus whiffiagonis; angler, Lophius … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Moisture and total lipid contents ranged from 828 to 845 and 3.0 to 3.7 g kg À1 muscle (Table 2), respectively, in good agreement with the results reported in previous research carried out on angler muscle (Jhaveri et al, 1984;Barros-Velá zquez et al, 2008;García-Soto et al, 2011). Total lipid range can be considered low compared to the lipid ranges of other lean fish species such as hake (Merluccius merluccius) (Aubourg et al, 1999) and turbot (Psetta maxima) (Aubourg et al, 2007).…”
Section: General Composition Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…Moisture and total lipid contents ranged from 828 to 845 and 3.0 to 3.7 g kg À1 muscle (Table 2), respectively, in good agreement with the results reported in previous research carried out on angler muscle (Jhaveri et al, 1984;Barros-Velá zquez et al, 2008;García-Soto et al, 2011). Total lipid range can be considered low compared to the lipid ranges of other lean fish species such as hake (Merluccius merluccius) (Aubourg et al, 1999) and turbot (Psetta maxima) (Aubourg et al, 2007).…”
Section: General Composition Analysissupporting
confidence: 88%
“…Preliminary research into quality changes in this species during storage or technological processing has assessed microbial presence (Mediel et al, 2000), volatile amine formation (RuizCapillas and Horner, 1999), nucleotide degradation (Mendes et al, 2001) and employment of advanced chilling strategies ( BarrosVelá zquez et al, 2008;García-Soto et al, 2011). Previous research related to chemical composition and nutritional value of angler is scarce and has focused on proximate and amino acid composition (Jhaveri et al, 1984), fatty acid composition (Sirot et al, 2008), and assessment of a-tocopherol and essential minerals (Jhaveri et al, 1984;Carvalho et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A progressive formation ( P < 0.05) of FFA was observed with chilling time in samples from each batch (Table ), and the values that were attained agree with previous research that showed a high FFA formation in megrim muscle during chilled storage (Aubourg et al ., ; García‐Soto et al ., ). Some significant differences ( P < 0.05) were observed as a result of the icing system employed; however, a definite trend concerning the icing effect could not be concluded because a higher formation was observed in the C‐125 batch during the 6–9‐day period, whereas batch‐175 fish revealed the highest FFA content at day 13.…”
Section: Resultsmentioning
confidence: 97%
“…For example, lipid oxidation was inhibited in Chilean jack mackerel as a result of including an oregano and rosemary extract in the icing system (Quitral et al ., ) and sardines by including a rosemary extract (Özyurt et al ., ). Directly related to the present research, the employment of a commercial formula including CA, LA and AA led to a lower oxidation development during the chilled storage of different fish species, including hake, megrim and angler (García‐Soto et al ., ) and blue whiting (Sanjuás‐Rey et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation